Renewable energy sources: Comparison of their use and respective policies on a global scale - (:unkn) unknown (IGI Global, 2016)
Sustainability concerns resulting from the consumption of natural resources, life-threatening levels of pollution, global warming, climate change and the ever-increasing worldwide energy use have brought renewable energy sources to forefront. Given the possibility of depletion of fossil fuels in the near future, the utilization of clean and renewable energy sources have become inevitable. Consequently, governments and global organizations adopted respective regulations to ensure the production and use of renewable energy and promote the respective new investments. In the light of these developments, the aim of this study is to conduct a detailed review and evaluation on the current literature and global energy statistics. The respective projects, binding regulations, incentives, and pricing mechanisms have also been studied to analyze and compare the renewable energy policies adopted worldwide. Ultimately, the goal is to make certain suggestions and lay out possible solutions regarding global energy problems. © 2016 by IGI Global. All rights reserved.